Knowledge and attitude of Kenyan healthcare workers towards pandemic influenza disease and vaccination: 9 years after the last influenza pandemic. Issue 29 (29th June 2021) - Andayi, Fred; Emukule, Gideon O.; Osoro, Eric; Ndegwa, Linus K.; Otiato, Fredrick; Muturi, Peter; Azziz-Baumgartner, Eduardo; Kalani, Rosalia; Anyango, Edwina; Muthoka, Philip M.; Ebama, Malembe S.; Bresee, Joseph; et al.
Abstract: Background: Healthcare workers (HCWs) are at high risk of exposure and transmission of infectious respiratory pathogens like influenza. Despite the potential benefits, safety and efficacy of influenza vaccination, vaccines are still underutilized in Africa, including among HCWs. Method: From May-June 2018, we conducted a cross-sectional, self-administered, written survey among HCWs from seven counties in Kenya and assessed their knowledge attitudes and perceptions towards pandemic influenza disease and vaccination. Using regression models, we assessed factors that were associated with the HCW's knowledge of pandemic influenza and vaccination. Results: A total of 2, 035 HCWs, representing 49% of the targeted respondents from 35 health facilities, completed the question. Sixty eight percent of the HCWs had ever heard of pandemic influenza, and 80.0% of these were willing to receive pandemic influenza vaccine if it was available. On average, Kenyan HCWs correctly answered 55.0% (95% CI 54.0–55.9) of the questions about pandemic influenza and vaccination. Physicians (65.6%, 95% CI 62.5–68.7) and pharmacists (61.7%, 95% CI 57.9–65.5) scored higher compared to nurses (53.1%, 95% CI 51.7–54.5). HCWs with 5 or more years of work experience (55.8, 95% CI 54.5–57.0) had marginally higher knowledge scores compared to those with less experience (53.9%, 95% CI 52.5–55.3). Most participants who were willing to receive pandemic influenza vaccine did so to protect their relatives (88.7%) or patients (85.9%). Conclusion: Our findings suggest moderate knowledge of pandemic influenza and vaccination by HCWs in Kenya, which varied by cadre and years of work experience. These findings highlight the need for continued in-service health education to increase the HCW's awareness and knowledge of pandemic influenza to increase acceptance of influenza vaccination in the case of a pandemic.